Inflow of Foreign Direct Investment (Fdi) and Management Approaches of Multinationals in Nigeria - Cosmas C. Alugbuo; Dr. Aham Ikwumezie; Dr. Chigozie Ugochukwu Okoro (Research Parks Publishers, 2022)
The study investigated the implication of foreign direct investment flows in the prevalence of management approaches in thirty multinational organizations in Nigeria. The multivariate regression analysis was employed for the identification of factors in the Nigeria investment environment (other than fiscal performance) that may have strong mediating impact. Results from the analysis showed that the predominant staffing strategy in most multinational organizations with FDI presence skew to polycentric (β = 0.28; p < 0.05) staffing approach more than to ethnocentric (β = 0.03; p < 0.05). This can be explained by the prevalence of host country staffers occupying strategic position in host country’s offices. Manager’s perception of employee effectiveness is largely influenced by the employee level of aptitude and the employee tacit personality traits.